On partial spectrum sharing of two licensed networks using cognitive radios - Jiang, X; Zhang, Y; Wong, K; Edwards, D (2011)
Cognitive radio (CR) is an enabling technology that allows the unlicensed users to opportunistically access the licensed spectrum bands, without any modifications or updates for the licensed systems. In this paper, we first propose a new spectrum sharing policy, which achieves efficient spectrum sharing between two licensed networks. Then, a Markov chain model is developed to analyze the proposed spectrum sharing policy in the cases with and without spectrum handoff. Numerical results show that the proposed policy achieves a higher overall throughput of the two networks. Extensive simulations verify the analytical model. © 2011 IEEE.